Changes in the Prevalence and Severity of Recurrent Wheezing in Infants: The Results of Two Surveys Administered 7 Years Apart - Mallol-Villablanca, E; Aguirre-Camposano, V (Taylor and Francis Ltd, 2018)
Objective:To identify changes in the prevalence and severity of recurrent wheezing (RW) in infants using data obtained from two surveys administered seven years apart. Methods: A cross-sectional, international, population-based study in infants aged 12–15 months was conducted. Data were obtained from two surveys (S1 and S2, in 2005 and 2012, respectively) using the same methodology in three large Latin American cities: Curitiba (Brazil), São Paulo (Brazil), and Santiago (Chile). Results: A decrease in the overall prevalence of RW was identified between S1 (23.3%) and S2 (20.4%), p = 0.004, but it was mainly driven by the reduction observed in São Paulo; in Curitiba and Santiago, this change was not significant. The mean prevalence of the following RW severity indicators remained high and stable: severe wheezing episodes (56.9% in S1 and 54.2% in S2, p = 0.32) and emergency department (ED) visits for wheezing (S1 = 68.1%, S2 70.9%, p = 0.21). A significant increase in admissions for wheezing (21.1% to 26.7%, p = 0.004) was observed. In Curitiba and São Paulo, there were significant increases in the prevalence of physician-diagnosed asthma and in the use of inhaled corticosteroids and oral antileukotrienes. Conclusions: The prevalence and severity of RW during the first year of life remained high over time, with remarkably high rates of ED visits, admissions for wheezing and use of asthma medications. This study suggests the need for considering early asthma diagnosis and to establish an appropriate treatment in infants with recurrent and severe asthma-like symptoms. © 2017, © 2017 Taylor & Francis Group, LLC.